PENGEMBANGAN E-LKPD MENGGUNAKAN LIVEWORKSHEET PADA SUBTEMA 3 USAHA PELESTARIAN LINGKUNGAN - Sheren Eriska Priscilia Listy; Dadang Kurnia; Yudhie Suchyadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Literacy is a critical skill that is for enhancing understanding, communication, andparticipation in modern society. Libraries, as one of the primary sources of information,play a crucial role in promoting literacy across various segments of society. This journalaims to explore and analyze the role of libraries in literacy development, with a focus onvarious strategies and innovations employed by libraries to enhance literacy. Literacyskills serve as a fundamental foundation in education, enabling students to access,comprehend, and interact with the information necessary for daily life. Libraries, ascenters of information resources, play a central role in assisting students in developingtheir literacy skills. This research aims to investigate and analyze how the utilization oflibraries can significantly contribute to the development of literacy skills among students.